Expresión 13: left parenthesis, "x" minus "h" , right parenthesis squared plus left parenthesis, "y" minus "k" , right parenthesis squared equals "r" squaredx−h2+y−k2=r2
13
Expresión 14: "h" equals 0h=0
negative 10−10
1010
14
Expresión 15: "k" equals 0k=0
negative 10−10
1010
15
Expresión 16: "r" equals 155r=155
negative 10−10
155155
16
Expresión 17: left parenthesis, "x" minus "h" , right parenthesis squared plus left parenthesis, "y" minus "k" , right parenthesis squared equals "r" squaredx−h2+y−k2=r2
17
Expresión 18: "h" equals 0h=0
negative 10−10
1010
18
Expresión 19: "k" equals 0k=0
negative 10−10
1010
19
Expresión 20: "r" equals 162.5r=162.5
negative 10−10
162.5162.5
20
Expresión 21: left parenthesis, "x" minus "h" , right parenthesis squared plus left parenthesis, "y" minus "k" , right parenthesis squared equals "r" squaredx−h2+y−k2=r2